Long term outcomes among African stroke survivors: 4 years follow up data from the CogFAST—Nigeria Study - Ogunde, Gabriel; Akinyemi, Joshua; Allan, Louise; Owolabi, Mayowa; Ogunniyi, Adesola; Kalaria, Rajesh N.; Akinyemi, Rufus (Frontiers in Stroke, 2025)
IntroductionAlthough stroke is recognized as a chronic condition, estimates of different long-term outcomes after stroke are lacking in Africa. This study aimed to explore the profile, trajectory and determinants of long-term outcomes up to 4 years in a cohort of African stroke survivors.MethodThe data analyzed were collected in a longitudinal study of stroke survivors who were prospectively recruited into the CogFAST-Nigeria Study from two specialist hospitals in Nigeria. Subjects with subarachnoid hemorrhage, co-morbid psychiatric or neurologic illness, or any systemic disease that could impair cognition were excluded from the study. Cognition was assessed using the Vascular Neuropsychological Battery, depression with the Geriatric Depression Scale—short form, and functional performance with the Barthel Index. Weibull survival model, generalized estimating equation and linear mixed models were used to identify the predictors of mortality, cognitive impairment, functional performance, and caregiver burden respectively.ResultOf the 253 stroke survivors that were recruited into the study, 157 (59.7%) were males while the overall mean age was 60.2 ± 9.8 years.The proportions of those with cognitive impairment were 126/251 (50.2%) at 3 months after stroke, 69/160 (43.1%), and 12/36 (33.3%) at 1st and 4th year respectively, while the proportion of those with depression was 39.3% at 3 months post-stroke, 35.2%, and 36.1% at year 1 and 4 respectively. Cumulative Mortality increased from 13.8% (95% CI = 10.08–18.63) at 9 months post-stroke to 45.3% (95% CI = 39.42–51.6) at 4 years follow-up. The only factor associated with mortality after adjusting for ethnicity was working as an artisan (aHR = 2.22; 95% CI = 1.77–4.02). History of previous stroke increased the likelihood of functional dependency (OR = 2.17; 95% CI = 1.19–3.95). Meanwhile, higher education (OR = 0.05; 95% CI = 0.02–0.16) protected against cognitive impairment while previous stroke (OR = 2.17; 95% CI = 1.19–3.95;) and higher caregiver burden (OR = 1.02; 95% CI = 1.01–1.02) were associated with increased risk.ConclusionImproving stroke treatment and rehabilitation is crucial, especially for those with prior stroke, as it strongly predicts poor functional and cognitive outcomes.